2020
DOI: 10.1001/jamanetworkopen.2020.4088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Internal Medicine Physician or Multidisciplinary Team Comanagement of Surgical Patients and Clinical Outcomes

Abstract: IMPORTANCE Older patients who undergo surgery may benefit from geriatrician comanagement. It is unclear whether other internal medicine (IM) physician involvement improves outcomes for adults who undergo surgery. OBJECTIVE To evaluate the association of IM physician involvement with clinical and health system outcomes compared with usual surgical care among adults who undergo surgery. DATA SOURCES MEDLINE, Embase, CINAHL, and CENTRAL databases were searched for studies published in English from database incept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 47 publications
0
24
0
1
Order By: Relevance
“…Across the United States, advances in surgical technique and multidisciplinary care [38] have been shown to improve outcomes after elective TJA. The average hospital LOS in the United States after THA was 1.9 days, and it was just 1.0 day following TKA in 2020 [39].…”
Section: Bodymentioning
confidence: 99%
“…Across the United States, advances in surgical technique and multidisciplinary care [38] have been shown to improve outcomes after elective TJA. The average hospital LOS in the United States after THA was 1.9 days, and it was just 1.0 day following TKA in 2020 [39].…”
Section: Bodymentioning
confidence: 99%
“…Surgical patient co-management provided by IMPCT has been an essential part of implementing perioperative biomarker testing, and this model may confer addition benefits for patients, colleagues, and budgetary considerations. While co-management has not shown universal improvement in outcomes, 18 metaanalyses of shared care by geriatricians and orthopedic surgeons have showed decreased mortality and shorter length of stay (LOS). 19,20 Similarly, a meta-analysis of surgical patients with IM co-management demonstrated decreased LOS and mortality.…”
Section: The Vancouver General Hospital Modelmentioning
confidence: 99%
“…19,20 Similarly, a meta-analysis of surgical patients with IM co-management demonstrated decreased LOS and mortality. 18 An RCT looking at co-management by hospitalists and surgeons versus a consultation care model showed decreased minor, but not major, complications and fewer discharge delays. 21 Studies have also shown that shared care models increase prescribing of evidence-based treatment, 22 increase surgeon and nurse satisfaction, 21 decrease LOS 19,20,23 , and decrease readmissions resulting in overall cost savings.…”
Section: The Vancouver General Hospital Modelmentioning
confidence: 99%
“…Collaborative care models have shown better care coordination, 29,31 decreased complications including delirium and functional decline, 31,32 shorter hospital stays 31,32 and potential cost savings 33 . Observational data from the National Emergency Laparotomy Audit (NELA) in the United Kingdom (UK) show that postoperative geriatrician review is associated with lower mortality in older emergency laparotomy patients, 34,35 while meta‐analyses of studies of co‐management of surgical patients by geriatricians 36 or general physicians 37 suggest that mortality benefits accrue in models including a multidisciplinary team in addition to the medical specialist. There are also concerted efforts on improving perioperative care for older people undergoing elective surgery, proactively identify issues in the preoperative setting to predict and reduce complications postoperatively.…”
Section: Evidence For Collaborative Perioperative Care Of Older Peoplementioning
confidence: 99%